Strategi Humas Polsek Bendahara Dalam Menciptakan Citra Positif Dimata Masyarakat Pasca Kasus Tewasnya Pelaku Dugaan Penyalahgunaan Narkotika - Nadia Muharman; Zakirah Azman; Tari Aulia Sari (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
This study entitled "Public Relations Of Bendahara Sector Police's Strategies In Creating A Positive Image In The Eyes Of The Public After The Death Of The Alleged Drug Abuse Perpetrator Case" with the aim of finding out the strategies carried out by the Bendahara Sector Police's Public Relations in creating a positive image in the public after the death of the alleged perpetrator of Narcotics abuse. This research is a descriptive study with a qualitative approach. The data collection technique in this study was done by using interviews with the head of Public Relations of the Bendahara Sector Police and the General Section Chief Public Relation of Bendahara Sector Police. The determination of informant was chosen using a purposive sampling technique. The results showed that there were seven PR strategies used by the Public Relations of the Bendahara Sector Police, namely visiting victims' families regularly, approaching community leaders, counseling in turns to villages, saweusikula (visiting schools) activities, approaching Aceh Tamiang news journalists, uploading activities documentation to social media, and providing donations and assistance to local communities in need. There were several obstacles for the Public Relations of the Bendahara SectorPolice in carrying out the strategies that had been designed, namely the lack of facilities and the lack of personnel in charge of the Public Relations sector or department.